140k views
4 votes
Here is my problem. Hopefully you will be able to help me!

Here is my problem. Hopefully you will be able to help me!-example-1

1 Answer

3 votes

All the items use the same form of exponential equation:


f(t)=ab^t

In this form, the initial value is always "a", because for t = 0:


f(0)=ab^0=a

And whether it is a exponential growth of decay we can see by the "b" value.

It is an exponential growth if:


b>1

And it is an exponential decay if:


0Now, for the alternatives.<p>a)</p>[tex]\begin{gathered} a=2 \\ b=(2)/(5) \end{gathered}

So the initial value is 2 and "b" is less than 1, so it is an exponential decay.

b)


\begin{gathered} a=2 \\ b=(5)/(3) \end{gathered}

So the initial value is 2 and "b" is greater than 1, so it is an exponential growth.

c)


\begin{gathered} a=(2)/(3) \\ b=3 \end{gathered}

So the initial value is 2/3 and "b" is greater than 1, so it is an exponential growth.

d)


\begin{gathered} a=(2)/(3) \\ b=(1)/(3) \end{gathered}

So the initial value is 2/3 and "b" is less than 1, so it is an exponential decay.

e)


\begin{gathered} a=(3)/(2) \\ b=(2)/(3) \end{gathered}

So the initial value is 3/2 and "b" is less than 1, so it is an exponential decay.

User Daniel Kessler
by
5.5k points